Cost of Care Insights through Data Integration: Building Foundational Systems for Healthcare Analytics - Inukonda, Jaishankar (International Journal of Health Sciences, 2025)
Purpose: The article illustrates that data integration will play a pivotal role in value-based healthcare, amplifying the power of the best cost management and improving outcomes. It brings into focus the fundamental systems, methodologies, and best practices for integrating diverse sources of data that enable insight into action, driving cost efficiency and quality care. Methodology: The Article systematically reviews foundational systems and technologies essential for cost-of-care analytics in healthcare, with a focus on data integration frameworks such as HL7 and FHIR [9]. Different strategies for integrating these disparate data sources have been explored, including data warehousing and cloud-based solutions. Major challenges identified and analyzed in this article include data privacy, standardization, and organizational resistance to implementation. On the other hand, the best practices for the implementation process have been explored, including staged adoption, stakeholder engagement, and investment in leading analytics tools. Findings: Data integration in value-based healthcare has to be undertaken for both cost efficiency and improved patient outcomes. This integration process does need interoperable systems and centralized repositories [14] [31]. Privacy concerns, standardization, and such challenges need to be overcome through phased implementation, stakeholder engagement, and advanced analytics tools. Unique contribution to theory, practice and policy: The article contributes to the theory by placing data integration at the center of value-based health care, thereby connecting analytics to cost and outcome optimization. In practice, it would provide actionable methodologies-including interoperable frameworks for data standardization and phased implementation-to ensure seamless integration. It illustrates best practices that outline how to overcome operational hurdles, such as resistance to change and fragmented systems. From a policy perspective, emphasis is placed on the adherence to regulations such as HIPAA, ensuring that patient data are used securely and in an ethical manner. Putting these findings together will bridge the gaps in theory, practice, and policy for cost-effective quality care.